The bioactive compounds, beneficial medicinal properties, and biotechnological prospects of Fomitopsis: a comprehensive overview - Karunarathna, Samantha C.; Patabendige, Nimesha M.; Kumla, Jaturong; Hapuarachchi, Kalani K.; Suwannarach, Nakarin (Frontiers in Cellular and Infection Microbiology, 2025)
Members of the genus Fomitopsis are medicinal mushrooms and a rich source of bioactive compounds with significant pharmacological and biotechnological potential. This paper provides a comprehensive review of their secondary metabolites, including polysaccharides, terpenoids, and phenolic compounds. In addition, their chemical structures and biological activities are described in detail. These compounds exhibit antioxidant, antimicrobial, anti-inflammatory, and immunomodulatory properties, with promising applications in cancer therapy, cardiovascular health, and immune modulation. Beyond medicine, Fomitopsis plays a crucial role in biotechnology, contributing to bioremediation, biofuel production, pharmaceutical development, and functional food innovation. By integrating traditional medicinal knowledge with recent scientific advances, this review highlights the biomedical significance and industrial relevance of Fomitopsis, underscoring its expanding role in health and environmental sustainability.